The indestructible brand : crisis management in the age of social media - Sharma, Venke; Kharas, Hushidar (SAGE Publications India Pvt Ltd ; SAGE Publications Inc, 2017)
Whether or not your brand is on social media, your consumers are. They are continuously sharing their good and bad experiences about your brand. Most brands are not prepared to deal with negative feedback which, if ignored, can spiral into a crisis. This book seeks to aid brand and business owners to structure organizations to be crisis-ready. Creating a crisis squad and a crisis playbook, envisioning various scenarios that can occur, and what the brand's response should be are some of the areas the book delves into. It also recommends preventive measures that can save brands from social embarrassment, and social listening strategies that can alert organizations to a problem before it becomes a crisis. When everything else fails and a crisis is at hand, the focus shifts to executing the playbook, turning the conversation around leveraging evangelists and influencers. Once the crisis has ended, it's time to audit the playbook and close the gaps, as well as evaluate financial or reputational damage done to the brand, and see how quickly one can recover.- Resumé vydavatel
Keywords: krizový management; produktový management; obchodní značky; public relations; sociální média; crisis management; product management; brand name products; social media; elektronické knihy; monografie; electronic books; monographs